KECEMASAN SEBAGAI PREDIKTOR INTENSITAS NYERI PADA PASIEN PASCA AKUPUNKTUR - Mei Rianita Elfrida Sinaga; Taufiqur Rohman (Optimal Nursing Journal, 2026)
Acupuncture is an effective complementary therapy for reducing pain, but the needle insertion procedure can induce anxiety that potentially affects the patient's perception of pain. Anxiety as a psychological response is suspected to play a role as a predictor of the pain intensity felt after acupuncture treatment. This study aims to analyze the role of anxiety as a predictor of pain intensity in patients post-acupuncture at Community Development Bethesda Yakkum Yogyakarta. This study uses a quantitative design with a correlational analytical approach. The sampling technique used was total sampling with a total of 30 respondents. The level of anxiety was measured using the Hamilton Anxiety Rating Scale (HARS) before the procedure, while the intensity of pain was measured using the Numeric Rating Scale (NRS) after the procedure. Data analysis used the Somers’ d test to examine the direction and strength of the relationship. The research results showed that the majority of respondents experienced severe anxiety (43.3%) and mild pain (56.7%). The Somers’ d test indicated a significant relationship between anxiety and pain intensity (p = 0.005) with a positive direction and moderate strength. Anxiety acts as a predictor of pain intensity in post-acupuncture patients, where higher anxiety levels correspond to greater perceived pain intensity.